When vitamin supplementation would make all the difference - Carvalho, Clara; Carmo, Filipa; Martins, Rosa; Matos, Eugénia; Torres, Erica; Rebelo, Mónica (BIRTH AND GROWTH MEDICAL JOURNAL, 2024)
Introduction: Dietary intake is insufficient to provide adequate levels of vitamin D during the first year of life and supplementation is required. The main function of calcitriol is to regulate calcium-phosphorus metabolism. Its deficiency can lead to hypocalcemia with severe clinical manifestations. Case Report: A six-month-old melanodermic female infant, exclusively breastfed until five months of age without cholecalciferol supplementation, was admitted for respiratory distress that progressed to severe bradycardia requiring resuscitation. Cardiac ultrasound was compatible with dilated cardiomyopathy, and the girl was admitted to the Intensive Care Unit. She later developed seizures, and neuroimaging was compatible with hypoxic-ischemic encephalopathy. Laboratory studies revealed hypovitaminosis D and hypocalcemia. Replacement therapy was initiated. Due to lack of improvement and poor prognosis, palliative care was provided, and the patient eventually died. Discussion/Conclusions: Vitamin D supplementation in the first year of life is essential to prevent calcium-phosphorus metabolism disorders and secondary cardiomyopathy, cardiogenic shock, and even death.